“you just look at rocks, and have beards” Perceptions of Geology From the United Kingdom: A Qualitative Analysis From an Online Survey - Steven L. Rogers; Sam Giles; Natasha Dowey; Sarah E. Greene; Rehemat Bhatia; Katrien Van Landeghem; Chris King (Earth Science, Systems and Society)
In the last few decades, Geology courses, particularly in the Global North, have seen a decline in student enrolment. Geologists have linked this downturn to a lack of exposure to the subject at school and college level. This work seeks to understand the public’s relationship with Geology and draws on over 5,000 open-ended question responses to a survey disseminated in 2021. The survey asked both those who had, and had not, studied geology as a subject a series of questions in order to explore their perceptions of the discipline. Our findings indicate that individuals “outside” of geology see the subject as old fashioned, boring, and environmentally damaging; simply the study of rock samples with nothing new to be discovered from; and with poor job prospects outside of the oil and gas industry. Geologists who responded to the survey paint a picture of a broad, interdisciplinary subject, with vibrant employability opportunities—yet struggle to coherently and collectively describe this when asked, “what is geology?”. In addition to the identified perception of geology as boring, and notions of poor employability being a barrier to prospective students, diversity and inclusivity issues are highlighted as significant barriers by those who study geology. Our findings indicate that both geologists and the geology curriculum need to coherently describe what geology is more effectively. We need to develop and better communicate the subject’s interdisciplinary nature and links to critical societal issues, such as the role of responsible mineral extraction in the energy transition and the importance of geology in vital areas such as climate change science, water resource management, environmental conservation, and sustainable urban/built development. Finding new ways to show that, far from being boring, geology is a subject that can fundamentally change the way you see and interact with the world around you is of central importance to achieving this. Efforts to make the subject more equitable are also highlighted as being critical in creating a more inclusive and accessible discipline.